Internal and External Learning Races in Born Transnationals: What are the Driving Forces? - Jörg Freiling; Mareike Zimmermann (Entrepreneurial Business and Economics Review)
This paper investigates an under-researched type of “born transnationals” as young transnational companies. “Born transnationals” are equipped with specific governance structures that may accelerate the internationalization process based on organizational learning. In this vein, the research question of the paper is: What are the core drivers of organizational learning in case of “born transnationals”?